2014
DOI: 10.1155/2014/529878
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Formal and Informal Home Care and Quality of Life for Patients with Multiple Sclerosis in Sweden

Abstract: Disease progression in multiple sclerosis leads to dramatic changes in a person's ability to perform daily activities and increases reliance on external help. This study aims to describe and to estimate costs of formal/informal home care and quality of life related to multiple sclerosis. A mailed survey to a random sample of MS sufferers (n = 1500) collected data on the number of hours of home care received, type of help, productivity losses, quality of life, and disease characteristics. Costs for home care we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…39 The absence of questions related to cognition and fatigue which are often major issues in people with progressive MS, has also been queried. 40,41 Several previous trials of mindfulness interventions have shown benefits upon psychological well-being in people with chronic conditions. 10 This pilot trial looked specifically at reducing distress, anxiety and depression for people with progressive MS as very few psychological interventions have focused specifically on this group of patients with MS. 9 The shorter duration of each session and the daily homework practice meant that the mindfulness course might be more accessible and manageable to this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The absence of questions related to cognition and fatigue which are often major issues in people with progressive MS, has also been queried. 40,41 Several previous trials of mindfulness interventions have shown benefits upon psychological well-being in people with chronic conditions. 10 This pilot trial looked specifically at reducing distress, anxiety and depression for people with progressive MS as very few psychological interventions have focused specifically on this group of patients with MS. 9 The shorter duration of each session and the daily homework practice meant that the mindfulness course might be more accessible and manageable to this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…39 The absence of questions related to cognition and fatigue which are often major issues in people with progressive MS, has also been queried. 40,41…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, costs not available in nationwide registers should also be accounted for, as part of the economic impact of MS, including long-term care, early mortality costs, and intangible costs resulting from MS [ 28 ]. Previous studies of bottom-up design, using patient inquiries, have identified resource use for both formal and informal home care [ 29 ], and intangible costs associated with MS relapses [ 30 ], which were not available in the current study. It has been reported that approximately 20% of patients changed residence due to MS and that 35% required assistance of more than 1 h daily [ 25 ].…”
Section: Discussionmentioning
confidence: 99%